Model independence of scattering of three identical bosons in two dimensions - Adhikari, Sadhan K. [UNESP]; Delfino, A.; Frederico, T.; Tomio, Lauro [UNESP] (American Physical Society (APS), 1993)
Within the framework of scattering integral equations in momentum space, we present numerical results of scattering of three identical bosons at low energies in two dimensions for short-range separable potentials. An analysis of the present numerical results reveals the three-particle scattering observables to be independent of potential shape provided the low-energy two-particle binding energy and scattering length are held fixed throughout the investigation. We think that the present conclusion of model independence will be valid for any potential, local or nonlocal, whose range is much smaller than the size of the two-particle bound state. © 1993 The American Physical Society.